Medieval church symbolism - Spurrell, Mark, author.
1 online resource
Keywords: "Medieval Church Symbolism: An Introduction explores the ways in which the Medieval church building and key features of it were used as symbols, particularly to represent different relationships within the Church and the virtues of living a Christian life"--